Simplified seismic analysis of one-way asymmetric elastic systems with supplemental damping. - Lin, Jui-Liang
This study investigates the effectiveness of the modal analysis using two-degree-of-freedom (2DOF) modal stick to deal with the seismic analysis of one-way asymmetric elastic systems with supplemental damping. The 2DOF modal stick possessing the non-proportional damping property enables the modal translation and rotation to not be proportional even at elastic state. The analytical results of one-storey and three-storey buildings obtained by the proposed method are compared with those obtained by direct integration of the equation of motion and conventional approximate method, which neglects the off-diagonal elements in the transformed damping matrix. It is found that the proposed simplified method, compared to conventional approximate methods, can significantly improve the accuracy of the analytical results and, at the same time, without obviously increasing computational efforts.
Keywords: Asymmetric building; Supplemental damping; Non-proportionally damping; Modal analysis; One-way asymmetric